Restaurer et transmettre la « magie » des coulisses des livres animés - Clémentine Desmond (Strenae)
The aim of this article is to present my job as a book conservator as indissociable: practical interventions are always drawn on scientific and historical observations. Being a specialist in movable book conservation for years made me realise that only the visible treatments were recorded and could be studied later on. However, numerous aspects are related to the context of creation of the object and are left behind without any complete documentation on the "behind the scenes". We hope that this paper will bring to light the conservation process as a whole which should be shared and preserved by all.